A “Nihilist Philosophy?”: Christian Orthodox Heretical Discourse and Japanese Buddhism in Greece - Gaitanidis, Ioannis (Journal of Religion in Japan, 2021)
Abstract Contrary to other European countries, where Buddhism has been studied since at least the 19th century, this paper shows that there are no known direct channels of transmission of Japanese Buddhism between Japan and Greece. Connections have, however, been made through other European countries, where, for example, Italy continues to play a major role. Moreover, these transmissions have taken a very long time to spread beyond the immediate circle of one or two key figures, because such traditions have been met with suspicion by the larger population, which remains influenced by a Christian Orthodox outlook. The establishment of Zen meditation centers in today’s urban centers, however, shows that the legal and official protections from which the Greek Church continues to benefit are not a reflection of devout sentiment among the population. This paper illustrates that under Greece’s conservative Orthodox climate, Japanese Buddhism has become simultaneously “Japanese culture” and a philosophy open to “all religions.”